State-Anxiety and Academic Burnout Regarding University Access Selective Examinations in Spain During and After the COVID-19 Lockdown - Fernández-Castillo, Antonio (Frontiers in Psychology, 2021)
Coping with assessment tests are known to generate anxiety frequently in the students who face them. In academic circumstances with the continued presence of emotional disturbance, high demand, and stress, emotional and physical fatigue, typical of burnout syndrome, can be detected. Anxiety and burnout are related to each other and even more closely in high-stakes tests. One of these tests is the examination imposed in Spain for access to the university. The objective of this work is to analyse the presence of anxiety and burnout and the relationship between them in students who face these tests, both during the confinement situation due to the COVID-19 pandemic and during the pandemic after the lockdown. For this purpose, we used a sample of 1021 students with a mean age of 17.89 (SD = 1.22, range 17-27). Of these, 866 (84.8%) were students who were taking the test, while the rest were university students who had passed it recently. Our results show high levels of anxiety and burnout in students who face the evaluation test during the COVID-19 pandemic, sustained over time and especially in comparison with students who had already taken the exam. The association between higher levels of anxiety and higher levels of burnout in the students who take these exams was also verified. These results link the relationship between these two variables more solidly and suggest the need to include address anxiety to reduce burnout levels in these students. The results are discussed with regard to prior evidence and their applications.